Hypospadias surgery in England: Higher volume centres have lower complication rates. Issue 5 (October 2017) - Wilkinson, David J.; Green, Patrick A.; Beglinger, Shanthi; Myers, Jessica; Hudson, Rachel; Edgar, David; Kenny, Simon E.
Summary: Introduction: Hypospadias surgery has progressed steadily over recent years. There remains considerable variation in the operative management of boys with hypospadias in the UK, and it is therefore difficult to identify acceptable standards with regards to reoperation rates. Objective: To determine the frequency of reoperations and complications from all centres performing hypospadias surgery in England and to identify variables that influence outcome. Methods: All children undergoing NHS hypospadias surgery in England between 1999 and 2009 were identified using the Hospital Episode Statistics database. Patient demographics, centre type, and associated diagnostic (ICD-10) and treatment codes (OPCS4.6) were collected for both primary repairs and postoperative complications. Centres were classed as high volume if they performed an average of 20 or more operations a year. Operative complications were split into revisions (repeat repairs), repairs of urethral fistulae, repairs of meatal stenosis, or urethral stricture repairs. Statistical analysis included logistic regression, Spearman's correlation, and Mann–Whitney U for non-parametric data, with p < 0.05 taken as significant. Data are presented as median (interquartile range) unless otherwise stated. Results: children underwent a total of 23, 962 operations at 75 centres in England during the study period. The median age at primary repair was 21 (15–38) months. The overall complication rate was 18.1%. The median complication rate for individual centres was 20.0% (13.9–27.4%) overall; 10.8% (4.7–15.9%) for revision procedures, 8.1% (5.5–11.7%) for urethral fistulae, 2.3% (1.1–3.7%) for meatal stenosis repairs, and 1.8% (0–2.8%) for urethral strictures. High volume centres had significantly lower complication rates than low volume centres (17.5% vs. 25%, p = 0.01) (Figure), and this was proven to be an independent predictor of outcomes ( p = 0.01). Staged repairs were associated with more complications ( p < 0.001); however, patient age and centre type were not. Median time to repair of complication was 13 (8–22) months. Discussion: This national population-based study used hospital episode statistics data. While accuracy is high and it has been validated for use in research, it has intrinsic limitations which affect our study. We are unable to fully account for the severity of hypospadias or the number of operating surgeons within institutions. Conclusions: This study has found a clear relationship between caseload volume and complications following hypospadias surgery. Furthermore, there is significant variability between centres in terms of their surgical outcomes. Taken together these results suggest that surgeons, particularly those in centres with small caseloads should assess their results against such benchmarks when evaluating the service they provide. Figure Difference in complication rates between high volume and low volume centres. There is a significant difference in complication rates between high volume and low volume centres (17.5% vs. 25%, p = 0.01).